From Cerebrospinal Fluid Pulsation to Noninvasive Intracranial Compliance and Pressure Measured by MRI Flow Studies - Alperin, Noam; Mazda, Monica; Lichtor, Terry; Lee, Sang H. (Current Medical Imaging, 2006)
The pulsation of the cerebrospinal fluid (CSF) has fascinated investigators of the intracranial physiology since it was first documented by invasive CSF pressure measurements. Advances in dynamic Magnetic Resonance Imaging (MRI) now enable visualization of and quantitation the CSF flow dynamics and has contributed to our understanding of the origin of CSF pulsation and its relation to the pulsatile blood flow. This, in turn, has led to the development of a noninvasive method for measurement of intracranial compliance and pressure by MRI. This article reviews the neurophysiologic and hydrodynamic principles that are the basis of the method, it describes the implementation of the method and validation studies to date with a non-human primate animal model, computer simulations, healthy human subjects and patients. The article further reviews the application of this method to study the effect of body posture on the cerebral physiology in humans through the relationships between blood and CSF flow dynamics. Finally, recent results from the application of the method in Chiari Malformations (CM) are briefly presented as an example of a potential clinical application of this methodology. The application to CM provided, for the first time, evidence of the important role intracranial compliance plays in the pathophysiology of this poorly understood disorder. The potential diagnostic value of an MRI-based measurement of ICP for other neurological problems is discussed.
Keywords: intracranial compliance